A Role for the Orphan Nuclear Receptor Estrogen-Related Receptor α in Endometrial Stromal Cell Decidualization and Expression of Genes Implicated in Energy Metabolism - Bombail, Vincent (The Endocrine Society, 2010)
Context: Differentiation (decidualization) of endometrial stromal cells (ESC) is an essential prerequisite for successful implantation and establishment of pregnancy. Objective: The aim was to determine whether the orphan nuclear receptor estrogen-related receptor α (ERRα, NR3B1), and its target genes, medium chain specific acyl-CoA dehydrogenase (MCAD, ACADM), pyruvate dehydrogenase kinase 4 (PDK4), and phosphoenolpyruvate carboxykinase 2 (PEPCK, PCK2), play a role in the decidualization process. Setting: We conducted the study at a University Research Institute. Patients and Methods: Endometrial tissues were collected from women with regular menstrual cycles; tissues were used for recovery of primary ESC or RNA extraction or were fixed for immunohistochemistry. Primary ESC were decidualized in vitro; some cells were treated with XCT790 (ERRα inverse agonist). Results: Decidualization of ESC in vitro was associated with a significant increase in expression of transcripts encoding ERRα and its coactivator peroxisome proliferator-activated receptor γ coactivator-1 α. Expression of ERRα target genes was altered with increased expression of MCAD and PDK4 and reduced expression of PEPCK. Incubation of decidualized ESC with XCT790 reduced expression of ERRα and markers of decidualization such as IGFBP-1. Conclusion: Increased expression of ERRα may play a role in altering the bioenergetics of decidualized ESC in preparation for implantation of the embryo and successful establishment of early pregnancy.